Application of the Jarimatika Method to Improve Student Learning Outcomes in Grade 3 Mathematics Subjects at State Elementary School 4 Sambik Bangkol Academic Year 2022/2023 - Fitriani, Titi Dwi Rahayu (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to determine whether the application of the Jarimatics method can improve student learning outcomes, in class III mathematics subjects, the subject of this research is class III at SDN 4 Sambik Bangkol sub-district. Gangga, with a total of 20 students. 8 male 12 female students, in this study used 2 cycles, each learning cycle used 2 meetings or 1 cycle was carried out for 2 days in the learning process with 2x35 minutes in 1 meeting. In this research, the method used is the classroom action method (PTK) carried out in 2 cycles, each cycle consisting of four stages, namely the planning stage, implementation stage, observation stage and reflection. In this research, data about student learning outcomes was obtained from the results of evaluations/tests carried out at the end of each cycle, while data about student and teacher learning activities in class were obtained from observation sheets. From the results of this research, it can be concluded that the application of the Jarimatika method can improve student learning outcomes in Grade 3 Mathematics at SDN 4 Sambik Bangkol. This increase can be seen from the students' average score of 54 in cycle 1 and increasing to 84.5 in cycle II, while the percentage of student learning completeness was 20% in Cycle 1, increasing to 100% in cycle II.